Prolonged response to treatment based on cell-free DNA analysis and molecular profiling in three patients with metastatic cancer: a case series. (March 2021) - Naqvi, Mohammad Faraz; Vo, Henry Hiep; Vining, David; Tsimberidou, Apostolia-Maria
Background: Patients with advanced and/or metastatic solid tumors have limited treatment options. Mutations that serve as biomarkers of carcinogenesis can be found in cell-free DNA of patients' plasma. Analysis of circulating tumor DNA (ctDNA) was developed as a non-invasive, cost-effective alternative to tumor biopsy when such biopsy is not technically feasible or it is associated with high risk for complications. The role of ctDNA in precision oncology is promising but its clinical significance across tumor types remains to be validated. We report a case series of three heavily pretreated patients with advanced solid tumors who received matched targeted therapy based on ctDNA analysis and/or tumor molecular profiling. Case presentation: Three patients with advanced, metastatic cancer and the following characteristics are presented: a 71-year-old woman with ovarian cancer and BRCA2 mutation identified in ctDNA and tumor tissue was treated with a PARP inhibitor and achieved partial response by RECIST (Response Evaluation Criteria in Solid Tumors) for 22.6+ months; a 40-year-old woman with adenoid cystic carcinoma of the parotid gland was treated with a MEK/RAF pathway inhibitor on the basis of RAF1 amplification on ctDNA analysis and had stable disease for 20.2 months; and a 56-year-old woman with breast cancer and a BRCA1 mutation identified by ctDNA analysis was treated with a PARP inhibitor and achieved stable disease for 9.1 months. All three patients are alive at the time of this report. Conclusions: These results suggest that ctDNA analysis can contribute to selection of targeted therapy in patients with advanced, metastatic cancer. Prospective clinical trials to evaluate and optimize ctDNA biomarkers, as well as the integration of novel and/or alternative targeted therapies, are warranted to fully assess the role of ctDNA analysis in cancer therapy. Trial registration: www.clinicaltrials.gov (NCT02152254). Registered May 28, 2014.https://www.clinicaltrials.gov/ct2/show/NCT02152254 . MD Anderson protocol # PA12-1161 (approval ID IRB1 FWA00000121) and # PA11-0377 (approval ID IRB4 FWA00005015).